Evaluation of nurses practices toward patients who undergo cardiac catheterization - Halim, abdel; Gourgees, Samira (Iraqi National Journal of Nursing Specialties, 2006)
Objective: To evaluate the nurse's practices and it's relationship between with thier demographic characteristic.Methodology: A descriptive study was carried out , from January 15th 2002 to April 15th 2002 , to evaluate thenurse’s practices toward patients who undergo cardiac catheterization . A purposive sample of ( 65 ) nurse , wasselected out of three teaching hospitals in Baghdad city . These nurses were worked at the catheterization unitsand catheterization labs .A questionnaire was constructed for the purpose of the study , which comprised of threemajor parts in which there were ( 45 ) items . Reliability and validity of the questionnaire were determinedthrough the conduct of a pilot study .Data were collected through the use of the constructed questionnaire as an observational tool and the observationtechnique as means of data collection .Data were analyzed through the use of two statistical analysis approaches : 1 - Descriptive statistical analysis that included frequencies and percentages . 2 - Inferential statistical analysis that include mean of scores , Alpha correlation coefficient and Chisquare .Result: Findings of the study indicated that there were no significant associations between the nurse’s practicestoward patients who undergo cardiac catheterization and their educational level and the nurse’s sex. Thepresent study concluded that all staff nurse had performed almost an equal level of practices regardless to theirsex and education and newly employed nurses had presented better practices that other .Recommendation: The study recommended that a well – formulated bill of standards should be created andpresented to all sites in which such practices are performed . Special training programs should be designed andconstructed for nurses in this area to reinforce their skills and promote their experience